Becoming a midwife: A survey study of midwifery alumni. Issue 3 (June 2019) - Patterson, Jean; Mącznik, Aleksandra K.; Miller, Suzanne; Kerkin, Bridget; Baddock, Sally
Abstract: Background: Becoming a competent midwife is a complex process. The aim of midwifery education is to support the development of competence in midwifery skills, knowledge and to prepare graduates to meet the responsibilities inherent in the midwifery role. Aim: To explore the experiences of our alumni midwives, ask how well they perceived their midwifery programme had prepared them for beginning midwifery practice and to identify any curriculum changes, or postgraduate study topics, that would support the transition to midwifery practice. Methods: An online survey was conducted with alumni of a Bachelor of Midwifery programme (New Zealand) who graduated between 2011 and 2014. The quantitative data were analysed using descriptive statistics, and a general inductive approach was used to develop themes from the qualitative data in the comment boxes. Findings: Forty-two alumni viewed becoming a midwife as a blend/combination of: (1) gaining the knowledge and practical skills required for the profession; (2) management skills in areas of running a business, working with other people, navigating local procedures and processes effectively, and balancing work with personal life; (3) gaining confidence in one's competence, and (4) having support along the way. Discussion: Competence in current evidence-based midwifery knowledge and practice is important in educating midwifery students. However, to transition to practice, a supportive environment is needed to assist midwives to develop self-management, business skills, and the confidence to negotiate and collaborate with colleagues and other health professionals. Conclusions: Not only did midwifery knowledge and practice skills matter for alumni, but also the acquisition of management skills, strategies for building confidence, and ongoing support. Content that facilitates these requirements should be included in midwifery programmes to support the transition from student to practitioner.